1992
DOI: 10.1159/000261481
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Clearance from Different Regions of the Mouth in Children

Abstract: The aim of this study was to evaluate the rates of salivary clearance at seven different locations in children. The diffusant was 1 mol/l KCl in a 1.0% agarose matrix, placed in small acrylic devices which could be fastened to the teeth with dental floss. The diffusion chambers were taken from the mouth at selected time intervals and the gels transferred quantitatively to flasks containing 400 ml of 100 ppm NaCl. The fluid was agitated intermittently for 1 h and analyzed for potassium by atomic absorption spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 11 publications
(19 reference statements)
1
9
0
2
Order By: Relevance
“…The clearance halftimes on the buccal surfaces of the upper anterior teeth were the longest of any site in the mouth. Weatherell, et al [2] and Watanabe [3] reported the same results. These show that the saliva secreted into oral cavity is not perfectly mixed.…”
Section: Introductionsupporting
confidence: 57%
“…The clearance halftimes on the buccal surfaces of the upper anterior teeth were the longest of any site in the mouth. Weatherell, et al [2] and Watanabe [3] reported the same results. These show that the saliva secreted into oral cavity is not perfectly mixed.…”
Section: Introductionsupporting
confidence: 57%
“…Among the salivary protective factors, the clearance of the saliva flow rate is one of the most important, not only because it removes endogenic/exogenic microorganisms, and their products, but also because a constant amount of saliva guarantees the presence of antimicrobials, immunological and non-immunological factors in the mouth 20 . Clearance of the saliva shows a direct correlation with the flow rate 21 therefore, individuals with reduced saliva flow rate show a greater quantity of Lactobacilli and S. mutans than those with a normal saliva flow rate 22 , which can increase the risk of mouth diseases. The phosphate concentration showed a reduction of about 27% in the overweight and obese children.…”
Section: Discussionmentioning
confidence: 99%
“…Forty newly erupted maxillary lateral incisors were cleaned (Hawe 0270 Latch X30) at slow speed (T1 LINE C 40 L, Sirona, Germany) with non‐fluoridated polishing paste (Cleanic, Kerr Corporation, Orange, CA, USA) for 10 s, gently washed for 40 s, air‐dried and then submitted to a first impression using a polyvinyl siloxane (PVS) impression material (Affinis light body; Coltene, Alstatten, Switzerland), expressed in three layers where the first layer had oil‐free air‐flow applied to the surface to improve the detailed reproduction by the impression material penetration (Baseline) (Gorton and Featherstone, ). Teeth were etched for 15 s with 37% phosphoric acid (Scotchbond, 3M UNITEK, St. Paul, MN, USA), ensuring that the etchant gel was isolated to the test site (Watanabe, ). After etching, the surfaces were rinsed with water from a three‐in‐one syringe for 40 s and another impression was taken using the PVS material (Baseline after etching, T0).…”
Section: Methodsmentioning
confidence: 99%
“…). It has been reported that the maxillary anterior labial site has the lowest salivary clearance in the oral cavity (Watanabe, ; Praxedes‐Neto et al …”
Section: Introductionmentioning
confidence: 99%